Testing the redintegration hypothesis by a single probe recognition paradigm. Issue 9 (21st October 2018) - Kowialiewski, Benjamin; Majerus, Steve
ABSTRACT: The lexicality effect in verbal short-term memory (STM), in which word lists are better recalled than nonwords lists, is considered to reflect the influence of linguistic long-term memory (LTM) knowledge on verbal STM performance. The locus of this effect remains, however, a matter of debate. The redintegrative account considers that degrading phonological traces of memoranda are reconstructed at recall by selecting lexical LTM representations that match the phonological traces. According to a strong version of this account, redintegrative processes should be strongly reduced in recognition paradigms, leading to reduced LTM effects. We tested this prediction by contrasting word and nonword memoranda in a fast encoding probe recognition paradigm. We observed a very strong lexicality effect, with better and faster recognition performance for words as compared to nonwords. These results do not support a strong version of the redintegrative account of LTM effects in STM which considers that these LTM effects would be the exclusive product of reconstruction mechanisms. If redintegration processes intervene in STM recognition tasks, they must be very fast, which at the same time provides support for models considering direct activation of lexico-semantic knowledge during verbal STM tasks.